2021
DOI: 10.3889/oamjms.2021.7759
|View full text |Cite
|
Sign up to set email alerts
|

Laportea decumana (Robx) Wedd. Herbal Endemic Potential from Indonesia: A Literature Review

Abstract: BACKGROUND: Indonesia with its tropical rainforest and its endemic flora, namely, Laportea decumana (Robx) Wedd. which is used as a traditional medicine. If we want to adopt it in complementary of nursing therapy as herbal medicine, it must be proven on an evidence-based. METHODS: The design in this study was a literature review article. Search for articles using relevant ones obtained from data based on Pubmed, Proquest, Ebsco, ScienceDirect, and Google Scholar in the span of the past 10 years (2011–2021) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…The present study discovered that Laportea decumana leaves contain an active compound known as 9-(buta-1,3-dien-2-yl)-11-hydroxy-2,2a,2b,3,4,5,6,6a,7,8,8a1,9,9a,12,12a,14b-hexadecahydro-1H,11H,14H-13-oxacyclobuta [1,5] cyclopenta [1,2a]cyclobuta[de]cyclopropa[b]chrysen-14-one (MCI). The compound has antibacterial activity against S. aureus, free radical scavenging activity, and cytotoxic activity on 4T1 breast cancer cells.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The present study discovered that Laportea decumana leaves contain an active compound known as 9-(buta-1,3-dien-2-yl)-11-hydroxy-2,2a,2b,3,4,5,6,6a,7,8,8a1,9,9a,12,12a,14b-hexadecahydro-1H,11H,14H-13-oxacyclobuta [1,5] cyclopenta [1,2a]cyclobuta[de]cyclopropa[b]chrysen-14-one (MCI). The compound has antibacterial activity against S. aureus, free radical scavenging activity, and cytotoxic activity on 4T1 breast cancer cells.…”
Section: Discussionmentioning
confidence: 70%
“…It is widely grown in Papua and Papua New Guinea and has been used as a herbal remedy to treat pain and headaches. 1 It has potential pharmacological activity due to the presence of alkaloid, glycoside, and triterpenoid contents. 2 Previous studies found that L. decumana extract has analgesic and antibacterial properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of them is the Laportea decumana (Roxb.) Wedd (Thalib et al, 2021) in Figure 1, was known as a native Papuan plant (Simaremare et al, 2022). Papuans have utilized itchy leaves as a painkiller, which they have been using for generations (Simaremare et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Natural therapy has been utilized since long ago, where the knowledge is obtained through generations so that it is known as traditional medicine in the community for local wisdom [1]. Nowadays, most of the world's population still relies on traditional medicines for healthcare purposes.…”
Section: Introductionmentioning
confidence: 99%